A Set of Finite Elements for 2D Analysis of Reinforced Concrete Foundations on Deformable Subsoil - Szajna, Waldemar St. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents a formulation and verification of a 2D soil - structure interaction model which enables the analysis of reinforced concrete shallow foundations under monotonic short-time loads. The structure supported by a deformable subsoil, whose elasto-plastic features are being considered. The structure model describes: the ability of crack creation, non-linear stress - strain characteristics of concrete and reinforcement and also reinforcement - concrete interaction. The foundation - subsoil contact model enables the identification of slide and adhesion zones.
Keywords: Soil - structure interaction; reinforced concrete; FEM; contact element